Arabic calligraphy in the face of digitization: A Reading on Function, Aesthetics and Identity - Benadda Hadj, Mohammed (Journal of Humanities & Social Sciences, 2025)
This study aimed to reveal the characteristics of Arabic calligraphy and identify its functional and aesthetic dimensions, in order to ascertain whether or not it is one of the best fonts ever, as well as identify some of the motives that allowed UNESCO to classify it within the list of intangible world heritage, and to achieve the objectives of the study, relying on the descriptive method, a number of results were reached, the most important of which are:-1 Arabic letters are distinguished from all foreign letters by the fact that they can be formed into any geometric shape, and their essence does not change, Unlike the letters of other languages, they are rigid and have a single shape. -2 The Arabic letter is used in arithmetic and astronomy, and the letters of other languages do not have the same. -3 Arabic calligraphy is a plastic art, with its distinctive elements and components, it can be used as letters, words and sentences, as formative elements that contribute to the construction of the painting.  4- Arabic calligraphy is used in religious architecture as a structural element, and it has been employed as a primary decorative element complementing Islamic motifs.-5 The creative touches of manual calligraphy remain the most impressive, compared to digital calligraphy, because they are charged with the spirituality and feelings of the calligrapher. The study concluded that Arabic calligraphy is considered one of the greatest scripts of all time due to its multiple functions and advantages, its new forms, and it deserves classification. It recommends the necessity of paying attention to calligraphers and opening the field for students to learn its rules and master its art, and investing in its vast domain, achieving global recognition in front of various artistic currents in the world.
Keywords: Arabic calligraphy; functional dimension; beauty; art; Digitization